Intakes of whey protein hydrolysate and whole whey proteins are discriminated by LC–MS metabolomics - Stanstrup, Jan; Rasmussen, Jakob E.; Ritz, Christian; Holmer-Jensen, Jens; Hermansen, Kjeld; Dragsted, Lars Ove (Metabolomics, 2014)
Whey protein improves fasting lipids and insulin response in overweight and obese individuals. Whey hydrolysate was recently shown to be more active than whole protein but the differences in metabolite profiles after intake remain unknown. This study discriminates plasma profiles after intake of four different whey protein fractions and establishes new hypotheses for the observed effects. Obese, non-diabetic subjects were included in the randomized, blinded, cross-over meal study. Subjects ingested a high-fat meal containing whey isolate (WI), whey concentrate hydrolysate (WH), α-lactalbumin or caseinoglycomacropeptide as the protein source. Plasma samples were collected at five time points and metabolites analysed using LC–Q-TOF–MS. Plasma concentrations of ten amino acids (AAs) were different between the meals. The plasma levels of AAs and AA derivatives were generally directly related to the AA composition of the meals. Highly elevated plasma levels of a number of cyclic dipeptides and other AA metabolites were found following intake of the WH meal and these metabolites are primary candidates to explain the superior insulinotropic effect of WH. The manufacturing process of WH caused oxidization of methionine to methionine sulfoxide which in turn caused in vivo generation of N -phenylacetyl-methionine and N -phenylacetyl-methionine sulfoxide. These two compounds have not previously been described in biological systems.